BARRIERS AND FACILITATORS FOR PEOPLE IN BME GROUPS ACCESSING PRE-HOSPITAL CARE AND CAUSES AND CONSEQUENCES OF ANY DIFFERENCES IN DELIVERY: SYSTEMATIC REVIEW AND NARRATIVE SYNTHESIS. Issue 5 (18th April 2015) - Windle, Karen; Siriwardena, A Niroshan; Barot, Mukesh; Essam, Nadya; Johnson, Mark; Kai, Joe; Ortega, Marishona
Abstract : Introduction: Research addressing inequalities has focused predominantly on primary and community care; few initiatives relate to the pre-hospital environment. We aimed to identify in the literature barriers or facilitators experienced by patients from BME communities in accessing pre-hospital care and to explore the causes and consequences of any differences in delivery. Methods: We conducted a systematic literature review and narrative synthesis. Electronic and journal hand searches from 2003 through 2013 identified relevant evaluative studies (systematic reviews, randomised controlled trials, quasi-experimental, case and observational studies). A researcher extracted data to determine characteristics, results and quality, each checked by a second reviewer. The main outcome measures were delays in patient calls, mortality rates and 30-days survival post discharge. Results: Eighteen studies met criteria for the review: two concerned services in England and Wales and 15 were United States based. Reported barriers to accessing care were generic (and well-known) given the heterogeneity of BME groups: difficulties in communication where English was the patient's second language; new migrants' lack of knowledge of the health care system leading to inappropriate emergency calls; and cultural assumptions among clinical staff resulting in inappropriate diagnoses and treatment. There were limited reported facilitators to improvement, such as the need for translation services and staff education, but the latter were poorly described or developed. Where outcomes were discussed, there was evidence for race-related disparity in mortality and survival rates. This could reflect differences in condition severity, delays between onset and initiation of calls, or the scope of response and assistance. Conclusion: The paucity of literature and difficulties of transferring findings from US to UK context identified an important research gap. Further studies should be undertaken to investigate UK differences in prehospital care and outcomes for BME groups, followed by qualitative approaches to understand barriers and enablers to equitable access.